The strength and durability of fly ash and quarry dust light weight foam concrete. (2020) - Gopalakrishnan, R.; Sounthararajan, VM; Mohan, A.; Tholkapiyan, M.
Abstract: This research work has been investigate on the foam concrete, which is an novel and very useful materials in construction industry, basically a cement mortar slurry with a maximum of 10% volume of foam. One of the main disadvantage of foam concrete is the large usage of river sand as a filler material, which leads to eco-friendly concrete. An experimental investigation has been done to effect of fly ash by partially replacing in cement from 0 to 50% and replacing river sand by quarry dust (0-50%) for various mixes. This research paper produce the compressive strength, split tensile strength and durability properties such as water absorption and permeability. From the investigation it have been concluded that the replacing partially 30% of fine sand b and quarry dust combination produced better quality results in par with the conventional foam concrete.